2009
DOI: 10.1124/jpet.108.148007
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Released by Gluten-Stimulated Celiac Disease-Specific Intestinal T Cells Enhances the Transepithelial Flux of Gluten Peptides

Abstract: Celiac sprue is a T-cell-mediated enteropathy elicited in genetically susceptible individuals by dietary gluten proteins. To initiate and propagate inflammation, proteolytically resistant gluten peptides must be translocated across the small intestinal epithelium and presented to DQ2-restricted T cells, but the effectors enabling this translocation under normal and inflammatory conditions are not well understood. We demonstrate that a fluorescently labeled antigenic 33-mer gluten peptide is translocated intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 44 publications
0
37
0
3
Order By: Relevance
“…It was shown that the use of antibodies to block IFN-␥ not only inhibits the activation of metalloproteinases and the influx of gluten peptides through the intestinal barrier but also deters mucosal injury (48,49). Previously, baked wheat products containing gluten that was hydrolyzed by lactic acid bacteria and fungal proteases during sourdough fermentation did not induce IFN-␥ (19) in vitro, thus yielding products that were safe for CD patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the use of antibodies to block IFN-␥ not only inhibits the activation of metalloproteinases and the influx of gluten peptides through the intestinal barrier but also deters mucosal injury (48,49). Previously, baked wheat products containing gluten that was hydrolyzed by lactic acid bacteria and fungal proteases during sourdough fermentation did not induce IFN-␥ (19) in vitro, thus yielding products that were safe for CD patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ has been illustrated as a key determinant in gut permeability as well as in inflammation in CD [8,9]. It has been found that IFN-γ secreted by gluten-activated celiac patient T cells, represents the primary effector of increased gluten peptide translocation during active disease [9]. Toxic gluten peptides have been reported to elicit an important immune response in the celiac intestine after regiospecific deamidation by an endogenous extracellular enzyme, transglutaminase 2 (TG2) [10].…”
Section: Gamma; Pi3k Inhibitorsmentioning
confidence: 99%
“…It has been assessed that the cytokine expression pattern in response to gluten is strongly dominated by Interferon-γ (IFN-γ) and that celiac patients show an increased expression of IFN-γ and a high number of TCD4 + IFN-γ-producing cells [7]. IFN-γ has been illustrated as a key determinant in gut permeability as well as in inflammation in CD [8,9]. It has been found that IFN-γ secreted by gluten-activated celiac patient T cells, represents the primary effector of increased gluten peptide translocation during active disease [9].…”
Section: Gamma; Pi3k Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise the prevention of the recruitment of lymphocytes targeting the chemokine receptor and ligand interactions e.g. CCR9 and CCL25 [40] and CXCR3 and CXCL10 [41] and the modulation of inflammation by monoclonal antibodies against TNF-α (Infliximab) [42] and IFN-γ [43] are another attractive therapeutic options for CD [44].…”
Section: Therapymentioning
confidence: 99%